Swelling and mechanical behavior of modified poly(vinyl alcohol)/laponite nanocomposite membranes - Nair, Shubhangi H.; Pawar, Kiran C.; Jog, Jyoti Prakash; Badiger, Manohar V. (Journal of Applied Polymer Science, 2007)
Nanocomposite (NC) membranes based on hydrophobically modified PVA and laponite were synthesized with varying laponite content in the feed. The incorporation of laponite in NC membranes was investigated by FTIR spectroscopy and thermogravimetric analysis. The swelling ratio of membranes was determined as a function of temperature and laponite content. Swelling studies of NC membranes exhibited the decrease in swelling with an increase in laponite content in the NC membranes. The swelling ratio of NC membrane with 20% laponite slightly increased with an increase in temperature. Dynamic mechanical analysis showed the systematic increase in storage modulus with laponite content, which indicates the enhancement of mechanical property upon laponite addition. There was also a decrease in the tan 6 peak values of NC membranes with an increase in laponite content in NCs. The permeabilities through NC membranes as a function of solute size and laponite content were studied and the results showed molecular screening based on size. The permeability of solute reduced due to the presence of well-dispersed laponite in the NC. (c) 2006 Wiley Periodicals, Inc.
Keywords: Dynamic mechanical analysis; laponite; membranes; nanocomposite hydrogel; poly(vinyl alcohol)

Study of dielectric behavior in PVDF/clay nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (E-Polymers, 2009)
A high dielectric permittivity nanocomposite based on poly( vinylidene fluoride) (PVDF) and organically modified clay is reported. The present work aims to study the effect of clay on dielectric behavior of PVDF. The dielectric permittivity study shows a remarkable enhancement in the permittivity of nanocomposites in the low frequency region. The obtained permittivity values fits quite well to the prediction of dielectric permittivity from Vo-Shi model, which takes contribution of interface to permittivity into account. This enhanced permittivity in nanocomposites is attributed to the presence of interfacial polarization. The interface effect is further studied with cole-cole plot analysis. The dielectric loss study of pristine PVDF shows two relaxations associated with segmental (glass transition relaxation) and crystalline chain relaxation. However in the PVDF/Clay nanocomposites crystalline relaxation peak disappears which is attributed to the formation of the beta phase in PVDF/clay nanocomposites.

Strong electric field modulation of transport in PVDF/MWCNT nanocomposite near the percolation threshold - Chanmal, Chetan; Deo, Meenal S.; Rana, Abhimanyu; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2011)
A nanocomposite comprising of multiwalled carbon nanotubes (MWCNT) embedded in ferroelectric Poly(vinylidene fluoride) PVDF polymer matrix is examined for electric field induced transport modulation. The pulsed laser deposition (PLD) grown thin films of the nanocomposite with different MWCNT content were characterized. When used as a channel layer in a field effect transistor configuration, a strong electric field modulation of the transport was realized just below the percolation threshold. We believe that this nanocomposite non-percolating channel concept can provide several opportunities for FET devices for organic electronics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Field effect device; pulsed laser deposition; PVDF; Scanning tunneling microscopy

Strong photo-response in a flip-chip nanowire p-Cu2O/n-ZnO junction - Deo, Meenal S.; Mujawar, Sarfraj; Game, Onkar S.; Yengantiwar, Ashish; Banpurkar, Arun G.; Kulkarni, Sneha; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Nanoscale, 2011)
Cu2O nanoneedles are synthesized on a copper substrate by a simple anodization and reducing ambient annealing protocol. ZnO nanorods are grown on ITO coated glass by a low temperature chemical route. The electronic and photo-response properties of the p-Cu2O/n-ZnO flip-chip heterojunction are then studied and analyzed. We show that the I-V characteristic is rectifying and the junction exhibits a good photoresponse (similar to 120% under 1 V reverse bias) under AM 1.5 (1 Sun) illumination. This nano-heterojunction photo-response is far stronger as compared to that of a pulsed laser deposited thin film p-Cu2O/n-ZnO heterojunction, which can be attributed to higher junction area in the former case.

Swift heavy ion induced formation of Al/polymer composite layer for low thermal emissivity in the IR range - Babrekar, Harshada A.; Jog, Jyoti Prakash; Mathe, Vikas L.; Avasthi, D. K.; Ojha, S.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2012)
Composites of polymers with aluminium were formed by swift high energy ions of 150 MeV, which are used as low thermal emissivity materials for infrared wavelengths between 8-14 mu m. Emissivity and dielectric constants were studied for these structures. A semi-empirical model has been established to obtain the relation between emissivity and dielectric constant. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: composites; dielectric constant; Swift heavy ion; Thermal emissivity

Synergistic mechanical response of Nylon 6/Trogamid (R) T blends - Ridhore, Amol; Jog, Jyoti Prakash (Journal of Applied Polymer Science, 2013)
Blends of semicrystalline Nylon 6 with a varying ratios of amorphous Nylon are studied for their morphological, thermal, dielectric, and mechanical behavior. Thermal analysis indicated a compositional dependant decrease in the melting and crystallization temperatures of Nylon 6. The blends exhibited a single compositional dependant glass transition temperature in dynamic mechanical thermal analysis and dielectrical relaxation spectroscopy over entire mixing ratio indicating miscibility between the blend components. The values of flexural modulus and tensile modulus of the blends are found to increase without significant loss in the impact properties. The water absorption of the blends is also lower than the values calculated by rule of mixtures. The observed synergistic behavior of the mechanical properties of the blends is indicative of presence of strong interactions in the blends components. (c) 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013
Keywords: blends; dielectric properties; mechanical properties; polyamides; Thermal properties

Surface tailored PS/TiO2 composite nanofiber membrane for copper removal from water - Wanjale, Santosh; Birajdar, Mallinath S.; Jog, Jyoti Prakash; Neppalli, Ramesh; Causin, Valerio; Karger-Kocsis, Jozsef; Lee, Jonghwi; Panzade, Prasad (Journal of Colloid and Interface Science, 2016)
Polystyrene (PS)/TiO2 composite nanofiber membranes have been fabricated by electrospinning process for Cu2+ ions removal from water. The surface properties of the polystyrene nanofibers were modulated by introducing TiO2 nanoparticles. The contact angle of the PS nanofiber membrane was found to be decreased with increasing concentration of TiO2, depicted enhanced hydrophilicity. These membranes were highly effective in adsorbing Cu2+ ions from water. The adsorption capacity of these membranes was found to be 522 mg/g, which is significantly higher than the results reported by other researchers. This was attributed to enhanced hydrophilicity of the PS/TiO2 composite nanofiber membranes and effective adsorption property of TiO2 nanoparticles. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: electrospinning; Metal ion adsorption; Nanofiber; TiO2; Water treatment/purification